A comparison of salvage infusional chemotherapy regimens for recurrent/refractory multiple myeloma. Issue 20 (6th July 2015) - Griffin, Patrick T.; Ho, Viet Q.; Fulp, William; Nishihori, Taiga; Shain, Kenneth H.; Alsina, Melissa; Baz, Rachid C.
<x xml:space="preserve">Abstract</x> BACKGROUND Despite the impact of proteasome inhibitors and immunomodulatory agents, infusional chemotherapy regimens continue to be used for patients with multiple myeloma. To the authors' knowledge, contemporary data regarding salvage chemotherapy regimens are sparse, with no direct comparisons. METHODS The authors performed a single‐institution study comparing 3 salvage chemotherapy regimens in 107 patients with recurrent/refractory multiple myeloma: dexamethasone, cyclophosphamide, etoposide, and cisplatin (DCEP) in 52 patients; bortezomib, thalidomide, dexamethasone, cisplatin, doxorubicin, cyclophosphamide, and etoposide (VTD‐PACE) in 22 patients; and cyclophosphamide, vincristine, doxorubicin, and dexamethasone (CVAD) in 33 patients. RESULTS Differences between treatment groups existed, including higher baseline creatinine for patients treated with CVAD (P<.001) and greater prior use of infusional chemotherapy for those receiving VTD‐PACE (P<.001). There was no significant difference in response noted among the 3 regimens: 55% overall (P = .18). For the intent‐to‐transplant population, a similar percentage were successfully bridged to transplant without further therapy (62%; P = .9). There was no difference in survival observed across the 3 regimens, with an overall median progression‐free survival of 4.5 months (95% confidence interval, 3.6‐5.5 months [P = .8]) and a median overall survival of 8.5 months (95% confidence interval, 6.1‐11 months [P = .8]). Furthermore, there was no statistically significant difference noted among clinically relevant adverse events, although there was a suggestion of fewer adverse events with DCEP. Patients treated with the intent to transplant had superior outcomes for response (odds ratio, 3.40; P = .01), progression‐free survival (hazard ratio, 0.28; P<.001), and overall survival (hazard ratio, 0.19; P<.001). CONCLUSIONS The 3 salvage regimens demonstrated similar responses, survival, and adverse events. Given the short response durations observed in the recurrent/refractory disease setting, infusional chemotherapy is best suited for cytoreduction before more definitive therapy is administered. Cancer 2015;121:3622–3630. © 2015 American Cancer Society.